Analisis Efisiensi Tataniaga Komoditas Jamur Merang di Desa Cirejag Kecamatan Jatisari Kabupaten Karawang - Dhiya Nida Ulhaq; Abubakar Abubakar; Suhaeni Suhaeni (Jurnal Ilmiah Wahana Pendidikan, 2021)
The purpose of the research is to find out the channels, institutions, functions of the trading system and the structure of market behavior, the income or profits obtained and the efficiency of the mushroom commodity trading system in Cirejag Village, Jatisari District, Karawang Regency. The research method used is a survey method. This study uses primary data and secondary data. Primary data is collected with interview techniques using a questionnaire. Research respondents are mushroom farmers and traders (middleman, wholesaler and retailer). Secondary data are obtained from various literature and related information sources. Sampling is determined by simple random sampling method for mushroom farmers and snowball sampling method for traders. The analysis technique used is farm income analysis, trading margin, farmer's share and profit-to-cost ratio. The results showed that there are 7 (seven) trading system channels for edible mushrooms, all of the institutions carry out the marketing function. Marketers are in a perfectly competitive market structure where the number of sellers and buyers is large and the products are identical. Straw mushroom farming is feasible and profitable because the ratio calculation in mushroom farming is more than one R/C > 1, is 1.58. The most efficient channel lies in channel one which is producer farmers directly to consumers, because in channel one there is no additional cost and the largest Farmer's Share value is 1.00 percent. The inefficient channel is located in channel seven (VII) because it has the largest total margin of Rp. 8,833 with the highest costs, the smallest Farmer's Share value is 0.77 percent, with a profit-to-cost ratio of 0.93.